SOCIAL TECHNOLOGY OF UNIVERSITY INTERACTION MANAGEMENT WITH STAKEHOLDERS AS A TOOL FOR INCREASING COMPETITIVENESS - T. Bolshunova (Вестник университета)
The article has been devoted to the possibilities of using an interdisciplinary approach of sociology of management to adapt the management system of an organization of high education to the challenges of the «external» and «internal» environment using the potential of the theory of stakeholders in order to harmonize interests and increase competitiveness. The necessity of using the basic elements of this theory in management practice has been substantiated. As an experiment, an experience in the development and implementation of social technology for the organization of interaction of Lipetsk State Technical University with stakeholders has been adduced. The algorithm, principles and tasks of interaction of the educational organization with stakeholders and its place in the strategic management of the University have been described. The possibilities of using the theory of stakeholders in the strategic management of the University have been considered.